2016
DOI: 10.1111/resp.12948
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of ezetimibe against Mycobacterium tuberculosis infection in type II diabetes

Abstract: Ezetimibe, which is a currently marketed drug, could hold promise as an adjunctive, host-directed therapy for TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Therefore, reduction of plasma lipids may not be fully effective at controlling latent TB. In fact, our previous study showed that another lipid-lowering agent, ezetimibe, known to inhibit cholesterol uptake into cells, was associated with a lower risk of latent TB in patients with diabetes [29][30][31]. Our current study shows that fenofibrate not only sustains the availability of intracellular lipids but also enhances dormant genes known to involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, reduction of plasma lipids may not be fully effective at controlling latent TB. In fact, our previous study showed that another lipid-lowering agent, ezetimibe, known to inhibit cholesterol uptake into cells, was associated with a lower risk of latent TB in patients with diabetes [29][30][31]. Our current study shows that fenofibrate not only sustains the availability of intracellular lipids but also enhances dormant genes known to involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 51%
“…9 In contrast, nonstatin lipid-lowering agents are unknown to have anti-TB effects, except ezetimibe, which has recently presented potential benefits. 42 Since statin users and nonstatin users were both likely to have dyslipidaemia and the former were older and had more comorbidities than the latter in this study, statins' effect on TB cannot simply be explained by hyperlipidaemia itself or the healthy user effect. 16 Even after controlling for timerelated biases and balancing certain variables in the matched subcohort analysis, the results remained significant.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, combined with a standard anti‐TB regimen, statin accelerates bacillary clearance in the lungs of mice . In contrast, nonstatin lipid‐lowering agents are unknown to have anti‐TB effects, except ezetimibe, which has recently presented potential benefits . Since statin users and nonstatin users were both likely to have dyslipidaemia and the former were older and had more comorbidities than the latter in this study, statins' effect on TB cannot simply be explained by hyperlipidaemia itself or the healthy user effect .…”
Section: Discussionmentioning
confidence: 79%
“…Another cholesterol-lowering drug, ezetimibe, has also shown potency against intracellular M.tb under hypoxic conditions (Tsai et al, 2017). Furthermore, the study also reported that patients receiving ezetimibe therapy exhibited a lower incidence of LTBI as well as intracellular lipid content, concomitant with reduced bacterial reservoirs (Tsai et al, 2017).…”
Section: Therapeutic Targeting Of Host Immunometabolismmentioning
confidence: 99%
“…Another cholesterol-lowering drug, ezetimibe, has also shown potency against intracellular M.tb under hypoxic conditions (Tsai et al, 2017). Furthermore, the study also reported that patients receiving ezetimibe therapy exhibited a lower incidence of LTBI as well as intracellular lipid content, concomitant with reduced bacterial reservoirs (Tsai et al, 2017). However, like statins but via a different mechanism, ezetimibe also has anti-inflammatory properties which downregulates nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) expression and monocyte chemotactic protein 1 (MCP-1) production albeit with a chance of increasing NO expression (Toshiyuki and Yasuchika, 2011).…”
Section: Therapeutic Targeting Of Host Immunometabolismmentioning
confidence: 99%